Carcinosarcoma of the Urinary Bladder: A Case Report - Limci Gupta; Jacqueline Elder (The Scientific World Journal)
Carcinosarcomas are rare tumours containing both malignant mesenchymal and epithelial elements. This reports presents a 70-year-old man with carcinosarcoma of the urinary bladder, which is proven histologically.